2021
DOI: 10.1177/09612033211062515
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine blood levels predicts flare in childhood-onset lupus nephritis

Abstract: Objective Low hydroxychloroquine (HCQ) blood levels are predictors of flare in adult lupus. Childhood-onset systemic lupus erythematosus (cSLE) has high morbidity with renal involvement in up to 80% of cases. The aim of this study is to determine the HCQ cut-off levels which predicts flare in childhood-onset lupus nephritis (LN). Methods Sixty LN patients on HCQ use for at least 6-months were prospectively evaluated at baseline (BL) and about 6-months later for cSLE flare and HCQ blood levels (ng/mL) measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Mok et al [ 24 ] reported that the prescribed HCQ dose also correlated significantly with baseline SLEDAI scores, indicating that higher doses were used for more active manifestations with serologic and clinical remission, and having therapeutic HCQ levels, a trend of lower disease activity and fewer incidences of flares were observed. Regarding renal survival, the probabilities of developing 1ry and 2ry end-points were higher in the HCQ group at 6 and 12 months as shown by Andrade Balbi et al [ 25 ], Lee et al [ 26 ], and Pons-Estel et al [ 27 ] who revealed higher recovery of renal function and lower probability of kidney failure after 6 months of HCQ treatment. In addition, HCQ can delay the development of renal damage in LN with lower disease activity and glucocorticoid doses than in patients who did not receive HCQ [ 27 ].…”
Section: Discussionmentioning
confidence: 78%
“…Mok et al [ 24 ] reported that the prescribed HCQ dose also correlated significantly with baseline SLEDAI scores, indicating that higher doses were used for more active manifestations with serologic and clinical remission, and having therapeutic HCQ levels, a trend of lower disease activity and fewer incidences of flares were observed. Regarding renal survival, the probabilities of developing 1ry and 2ry end-points were higher in the HCQ group at 6 and 12 months as shown by Andrade Balbi et al [ 25 ], Lee et al [ 26 ], and Pons-Estel et al [ 27 ] who revealed higher recovery of renal function and lower probability of kidney failure after 6 months of HCQ treatment. In addition, HCQ can delay the development of renal damage in LN with lower disease activity and glucocorticoid doses than in patients who did not receive HCQ [ 27 ].…”
Section: Discussionmentioning
confidence: 78%
“…Antimalarial treatment is considered a quality indicator in North America,59 with a large retrospective cSLE cohort (n=473) demonstrating antimalarial treatment to be associated with protection against new damage accrual 54. Hydroxychloroquine blood levels are inversely correlated with disease activity in cSLE,96 with low concentrations predictive of flare 97. The Task Force noted hydroxychloroquine toxicity to be rare in cSLE 98.…”
Section: Resultsmentioning
confidence: 99%
“…The Italian study by Moroni et al [ 60 ] showed that continuing HCQ after withdrawal of immunosuppressive agents was linked to reduced renal flares. Also, in a case series of pediatric LN under a prescribed HCQ dose of 4.0–5.5 mg/kg/day, a HCQ blood cut-off level under 1075 ng/mL was associated with increased flares [ 61 ]. The same trends have been described for adults with LN [ 62 ].…”
Section: Modifiable Risk Factors and Preventive Strategies For Lupus ...mentioning
confidence: 99%